2009
DOI: 10.1029/2008jg000853
|View full text |Cite
|
Sign up to set email alerts
|

Impact of manipulated drought and heavy rainfall events on peat mineralization processes and source‐sink functions of an acidic fen

Abstract: [1] Climate change models predict changes in precipitation patterns over the next several decades for northern temperate regions. Resulting fluctuations of the water level may drastically affect the source-sink functions of peatlands. Here, we manipulated the water table level in an acidic, minerotrophic fen using drying and rewetting experiments to simulate summer drought and heavy rainfalls to estimate changes in peat decomposition and source-sink functions. We found that carbon dioxide (CO 2 ) formation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 92 publications
5
67
0
Order By: Relevance
“…The analytical precision of radiocarbon measurements was better than 3‰ and is reported as [pMC] 56 . Activities of phosphatases, β-glucosidases, general hydrolases (lipases, esterases and proteases) and β-exoglucanase (cellulase) were determined for 0.1 g ml −1 soil suspensions at a predetermined substrate saturation using the model substrates methylumbelliferyl phosphate (MUF-P, 1 mM), methylumbelliferyl-β-gluco-pyranoside (MUF-β-Glc, 1.5 mM), diacetyl-fluorescein (FDA, 57 µM) and methylumbelliferyl-β-cellobiose (MUF-β-Cel, 287m µM), as described previously [57][58][59] . Absorption and fluorescence were measured using a DR 3800 spectrophotometer (Hach Lange) and a Quantifluor-ST fluorometer (Promega), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The analytical precision of radiocarbon measurements was better than 3‰ and is reported as [pMC] 56 . Activities of phosphatases, β-glucosidases, general hydrolases (lipases, esterases and proteases) and β-exoglucanase (cellulase) were determined for 0.1 g ml −1 soil suspensions at a predetermined substrate saturation using the model substrates methylumbelliferyl phosphate (MUF-P, 1 mM), methylumbelliferyl-β-gluco-pyranoside (MUF-β-Glc, 1.5 mM), diacetyl-fluorescein (FDA, 57 µM) and methylumbelliferyl-β-cellobiose (MUF-β-Cel, 287m µM), as described previously [57][58][59] . Absorption and fluorescence were measured using a DR 3800 spectrophotometer (Hach Lange) and a Quantifluor-ST fluorometer (Promega), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In previous investigations we could show that similar patterns for anaerobic CO 2 and CH 4 formation rates occurred at the fen site independent from seasonal shifts from peat obtained at C2 and D2 from 0-40 cm depth during 2006 and 2007 (Reiche et al, , 2009; and data not shown). Additionally, the pattern of aerobic CO 2 formation rates of these peat samples, measured in oxic microcosms over an incubation period of 24 hours (Reiche et al, 2009), also supported this classification.…”
Section: Microbial Formation Of Co 2 and Chmentioning
confidence: 99%
“…Based on these earlier investigations, peat was sampled at four locations in November 2006, from the middle to the southern part of the fen, following the hydrological gradient. Sampling locations were named C2, D2, sD1, M according to previous investigations (Reiche et al, 2009). The maximum distance between C2 and M was approximately 25 m. Peat obtained at C2 and D2 was dark brown to black in color and the degree of decomposition according to Von Post's humification scale (Clymo, 1983) was higher (moderately decomposed, H6-7) than for the brownish peat at sD1 and M (slightly to moderately decomposed H3-5) in the 0-40 cm depth zone, respectively.…”
Section: Peat Samplingmentioning
confidence: 99%
“…We therefore suggest that, despite the only small difference in soil water content of the drained and undrained treatment, the disappearance of sulphate in the undrained treatment may have been caused by reduction to sulphide, although a more detailed analysis of the soil biogeochemistry and redox status would be needed to confirm this. De Mars and Wassen (1999), for instance, showed that even minor differences in water level in Dutch and Polish mires could lead to considerable differences in soil redox status, which could lead to altered SO 4 concentrations, even for prolonged periods after restoration of water levels to their original position (Reiche et al 2009). …”
Section: S-additionmentioning
confidence: 99%
“…Climate models predict increased temperatures, increased summer drought and increased occurrence of extreme precipitation events for temperate regions (IPCC 2007). For fens in these regions, this means that the soil will be subjected to increased summer drought and alterations in water level dynamics (Dawson et al 2003;Reiche et al 2009). These effects have been shown to increase both N-and P-availability to plants (Olde Venterink et al 2002;Van Dijk et al 2004;Reiche et al 2009).…”
Section: Introductionmentioning
confidence: 99%